Chinese Legal Family - He, Qinhua. author. aut Link
XVII, 339 p. 6 illus., 1 illus. in color.
Keywords: This book primarily focuses on the origin, essence, characteristics, and fundamental content of the Chinese Legal Family, the development of the laws as they were instituted in China and other countries in the Chinese Legal Family—such as Japan, Korea, and Vietnam—the impact and the historical status of the Chinese Legal Family. The present version is the English translation, completed under the Translation Project of Chinese Academic Works sponsored by the Chinese Fund for the Humanities and Social Sciences (with some sections abbreviated). The book’s target audience primarily falls into two categories: those interested in traditional Chinese legal culture and the legal cultures of East Asian countries such as Japan, Korea, and Vietnam, and those who wish to conduct further in-depth research on the legal concepts, legal systems, legal institutions, legal procedures, legal education, and legal research of China and East Asian countries, as well as their characteristics and essence.